1992
DOI: 10.1177/009365092019002004
|View full text |Cite
|
Sign up to set email alerts
|

Friendship, Social Interaction, and Coping With Stress

Abstract: The experiment described in this article examined how interacting with a friend as opposed to a stranger in anticipation of a stressful event (giving an extemporaneous speech) affects coping. Results indicated that subjects perceived more social support after interacting with a friend than with a stranger. They were less depressed and were judged to be more confident during the extemporaneous speech after interacting with an opposite-sex friend than with an opposite-sex stranger. Specific verbal and nonverbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Additional outcomes include problem resolution (or reduction of problem severity), positive changes in one’s circumstances or successful adaptation to circumstances that cannot be changed (e.g., reduced rumination, positive reappraisal, acceptance), successful rebuilding (replacing features associated with the adversity with new and improved ones), and learning from the experience. This is consistent with research showing that support provision facilitates problem resolution (e.g., Lakey & Heller, 1988; Winstead, Derlega, Sanchez-Hucles, & Clarke, 1992), promotes effective coping and adjustment to economic disadvantage (Chen & Miller, 2012) and to trauma and disease (see Revenson, 2003; Uchino, 2004), and facilitates benefit finding and growth following negative life events (see Helgeson & Lopez, 2010). …”
Section: Pathways To Thriving Through Relationshipssupporting
confidence: 82%
“…Additional outcomes include problem resolution (or reduction of problem severity), positive changes in one’s circumstances or successful adaptation to circumstances that cannot be changed (e.g., reduced rumination, positive reappraisal, acceptance), successful rebuilding (replacing features associated with the adversity with new and improved ones), and learning from the experience. This is consistent with research showing that support provision facilitates problem resolution (e.g., Lakey & Heller, 1988; Winstead, Derlega, Sanchez-Hucles, & Clarke, 1992), promotes effective coping and adjustment to economic disadvantage (Chen & Miller, 2012) and to trauma and disease (see Revenson, 2003; Uchino, 2004), and facilitates benefit finding and growth following negative life events (see Helgeson & Lopez, 2010). …”
Section: Pathways To Thriving Through Relationshipssupporting
confidence: 82%
“…A study by Costanza, Derlega, and Winstead (1988) found that individuals who engaged in problem-solving talk, a type of self-disclosure, had higher success in reducing stress levels. In their study, Winstead, Derlega, Lewis, Sanchez-Hucles, and Clarke (1992) found that self-disclosure provider greater benefit to the individuals over silence. The reasons why individuals would engage in the expression of negative self-disclosure (venting) have been examined throughout various disciplines.…”
Section: Perceived Stressmentioning
confidence: 93%
“…Although this limits general-izability, we wished in these initial experiments to avoid cross-sex interactions in which support provision could possibly be interpreted by participants as displaying romantic or sexual interest on the part of the confederate (as in the case in which Clark & Mills, 1979, used male participants and female confederates to study desire for a communal relationship). In addition, past researchers have demonstrated that gender composition is an important moderator of the effects of support receipt (Derlega, Barbee, & Winstead, 1994;Winstead et al, 1992). A final reason for restricting our initial experiments to women was because of the argument that women's reactions to stressors rely more on support giving and receiving, namely, the "tend and befriend" response, rather than the "fight or flight" response more characteristic of men (Taylor et al, 2000).…”
Section: An Experimental Paradigm For Studying Support Visibility Effmentioning
confidence: 99%